Shaping inductor geometry for casting functionally graded composites. Issue 1 (4th January 2016) - Golak, Slawomir; Kordos, Mirosław
Abstract : Purpose: – The attractiveness of functionally graded composites lies in the possibility of a gradual spatial change of their properties such as hardness, strength and wear resistance. The purpose of this paper is to discuss the use of electromagnetic buoyancy to separate the reinforcement particles during the casting process of such a composite. Design/methodology/approach: – The basic problem encountered in the process of casting composites is to obtain electromagnetic buoyancy and simultaneously to avoid a flow of the liquid metal which destroys the desired composite structure. In this paper the authors present the methodology of numerical optimization of inductor geometry in order to homogenize the electromagnetic force field distribution. Findings: – The optimization method based on searching the solution subspace created by applying knowledge of the modelled process physics proved better than the universal local optimization methods. These results were probably caused by the complex shape of the criterion function hypersurface characterized by the presence of local minima. Practical implications: – Due to their characteristics, functionally graded composites are of great interest to the automotive, aerospace and defense industries. In the case of metal matrix composites casting techniques (as the presented one) are the most effective methods of producing functionally graded materials. Originality/value: – The paper presents the optimization of a new process of casting functionally graded composites in a low-frequency alternating electromagnetic field. The process involves problems that did not occur previously in the area of electromagnetic processing of materials. The paper proposes the use of special design of inductors to homogenize the electromagnetic force field.